The Impact of Microcredit Interest Subsidy Accessibility on Paddy Farms Performance - Widhiyanto, Iman; Nuryartono, Nunung; Harianto, Harianto; Siregar, Hermanto (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
Capital is required in farm to buy input such as fertilizer, pesticide, seed, land rent, labor wage, and to adopt the latest technology. To ease the burden of loan interest and to increase the access of farm to formal credit, the government provides interest subsidy for Food Security and Energy Credit (Kredit Ketahanan Pangan dan Energi, KKP-E). This study was aimed to analyze the impact of accessing KKP-E on paddy farmsâ performance. The methods used in this study are descriptive analysis and propensity score matching model. Accessibility of KKP-E in research location was able to increase fertilizer use of 16.98 percent, pesticide use of 40.23 percent, labor outside farm household use of 43.08 percent, production of 58 percent, productivity of 23.64 percent, and farm profit of 84.5 percent. This quite high increase in percentage was due to the reason that farm business scale in this study was categorized as small-scale business.